Kalbos elementų klasifikacija ir semantika - Pavilionis, R. (Kalbotyra, 1973)
The paper aims at proving that (1) linguistics does not and can not present the classification of the elements of language consistent from the logical point of view and (2) the problem of language models can be solved but in terms of information-processing approach. Delineation of the hypothesis of a continuous semantic system comprising both verbal and non-verbal meanings is given to provide arguments for the two theses of the paper.